Non-invasive ventilation in COVID-19-related acute hypoxemic respiratory failure: a narrative review - Luigi Aronne; Raffaella Pagliaro; Angela Schiattarella; Susan FM Campbell; Maria Vitale; Fabio Perrotta; Klara Komici; Germano Guerra; Andrea Bianco; Filippo Scialò; Vanvitelli - Monaldi COVID Group (Monaldi Archives for Chest Disease, 2025)
The high mortality rate and extended ventilator use associated with invasive mechanical ventilation in patients with severe COVID-19 have sparked a debate about the use of non-invasive respiratory support, such as high-flow nasal cannula, continuous positive airway pressure, and non-invasive ventilation (NIV), as treatment options. According to the European Respiratory Society and the American Thoracic Society clinical practice guidelines, NIV is recommended to prevent intubation in hypoxemic acute respiratory failure in patients with community-acquired pneumonia or early acute respiratory distress syndrome without major organ dysfunction. Central to this debate is the role of NIV in managing acute hypoxemic respiratory failure. However, there are concerns that NIV might delay the timely intubation and lung-protective ventilation in patients with more advanced disease, potentially worsening respiratory parameters due to self-inflicted lung injury. This review aims to explore the current literature, focusing on the rationale, patient selection, and outcomes associated with the use of NIV in COVID-19 patients with acute respiratory failure, to better understand its role in this context.